Perilaku Penjamah Makanan Kantin Sekolah Kajian Studi Bakteriologi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
1.In the mean time, especially in the developing countries and in the underdeveloped countries where there is the food sanitation is quite low, there for there is a need to do a spesific research based on the problem above. The aim of a research is to study the quality of food canteen of some primary schools of the Magelang city centre. The result shows that the food handler's attitude do not have a relation to their knowledge, especially in the context of their formal education background and experience in taking the food canteen. Secondly, the food handler's attitude do not have a relation to the training which was given by the special health teacher of the school (Guru UKS) significantly. Thirdly, the quality of food canteen of primary school which was made by the food handlers themselves are more higienic bacteriologically compare to the food canteen which was made by others. Fourthly, the quality of food canteen and its dishes do not have a relation to the food handler's attitude. Based on the results above, therefore there is a spesific advice to the Health Department, The Education Department and the Home Affair Department to increase the quality of their performance and the content of their job concerning the food canteen.